2015
DOI: 10.18052/www.scipress.com/ilshs.51.33
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work-Life Balance on Employees’ Job Satisfaction and Turnover Intention; the Moderating Role of Continuance Commitment

Abstract: Work-life imbalance has several negative impacts on employees' attitudes and behaviors and consequently influences organizations' performance and effectiveness. The purpose of this article is to investigate the impact of work-life balance (WLB) on employees' job satisfaction and turnover intention. Moreover, we study the moderating role of continuance commitment on job satisfactionturnover intention relationship. Regression analysis was used to analyze the data collected from 265 questionnaires completed by em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
6
12
1
5
Order By: Relevance
“…This result is agreed with (Hassan, 2014;Arshad & Puteh, 2015) who indicated that employees will stay in organizations that achieve a balance between work and life. Although Fayyazi & Aslani (2015) found that WLB has a negative relationship with ETI, however, their results revealed that manager's support was the only WLB practice that had a significant negative direct effect on ETI, as Job autonomy and schedule flexibility had insignificant effect on ETI. Additionally, Suifan, Abdallah, & Diab (2016) found only that the informal WLB practices which involve manager's support and job autonomy had significant effect on ETI.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This result is agreed with (Hassan, 2014;Arshad & Puteh, 2015) who indicated that employees will stay in organizations that achieve a balance between work and life. Although Fayyazi & Aslani (2015) found that WLB has a negative relationship with ETI, however, their results revealed that manager's support was the only WLB practice that had a significant negative direct effect on ETI, as Job autonomy and schedule flexibility had insignificant effect on ETI. Additionally, Suifan, Abdallah, & Diab (2016) found only that the informal WLB practices which involve manager's support and job autonomy had significant effect on ETI.…”
Section: Resultsmentioning
confidence: 83%
“…It is assumed that the happier the employees are in their personal life, the happier they are at work (Gachter, Savage, & Torgler, 2013;Meenakshi, Subrahmanyam, & Ravichandran, 2013). Accordingly, WLB is considered an essential factor that influences employee's intention to leave his/her organization (Meenakshi al., 2013;Fayyazi & Aslani, 2015). Therefore, the researcher proposes the following hypothesis:…”
Section: Work-life Balancementioning
confidence: 99%
“…perceiving higher levels of career sacrifice for returning to hometown) should make the family-related gains less attractive in pushing migrant workers to leave their organizations in host cities. Indirectly supporting this argument, existing research demonstrated that employees' perception of costs associated with leaving attenuated the facilitating effects of work-life balance and job satisfaction on their turnover intention (Fayyazi and Aslani, 2015). In a similar vein, Vandenberghe et al (2011) also theorized that the perceived sacrifice associated with quitting would counteract the facilitating effects of other push-to-leave forces.…”
Section: The Moderating Role Of Career-related Concernsmentioning
confidence: 96%
“…Work life balance menjadi masalah yang penting bagi perusahaan secara umum, Work life balance erat dengan turnover intention (Noor, 2011), penelitian berhasil menemukan temuan bahwa Work life balance berpengaruh positif dan signifikan terhadap turnover intention. Suifan, et al, (2016) menyebutkan Work life balance akan memiliki efek pada keinginan untuk keluar dari perusahaan jika tidak mendapakan dukungan dari atasan, serta tidak adanya otonomi kerja yang diberikan oleh perusahaan kepada karyawan, beberapa temuan penelitian ini juga sama halnya dengan penelitian Fayyazi & Aslani, (2015); Khan et al, (2014);Atiq, et al, (2017) Jurnal Ilmiah Manajemen Dan Bisnis, Vol. 20 No.…”
Section: Pembahasanunclassified